The influence of the proportion of foreign ownership and financial ratio on banking performance in Indonesia in the period of 2017-2019 - Yacobo P Sijabat; Heni Hirawati; Deni Ramdani (The Management Journal of Binaniaga, 2020)
This research examined the influence of foreign proportions in the shares of banking companies and financial ratios on the performance of companies listed on the Indonesia Stock Exchange in the period 2014-2018.The proportion of foreigners in a banking company uses a comparison of the total amount of foreign shares with the total share ownership.While the proxies of financial ratios are measured using several ratios, including Non-Performing Loans (NPL), Loan to Deposit (LDR), Capital Adequacy Ratio (CAR) and BOPO.Performance proxies are measured using ROA and ROE proxies. The method used is data panel regression using stata 13.0 software.The results of research on the proportion of foreign to the company's performance have a significant effect on ROA alone.Keywords: Banking Company, Financial Ratios, Proportion of Foreign Ownership